Field experience with the 8-HPV-type oncoprotein test for cervical cancer screening among HPV-positive women living with and without HIV in LMICs (2024)
ABSTRACT: Overexpression of HPV-oncoproteins E6 and E7 is necessary for HPV-driven cervical carcinogenesis. Hence, these oncoproteins are promising disease-specific biomarkers. We assessed the technical and operational characteristics of the 8-HPV-type OncoE6/E7 Cervical Test in different laboratories using cervical samples from HPV-positive women living with (WLWH) and without HIV. The 8-HPV-type OncoE6/E7 Test (for short: "OncoE6/E7 test") was performed in 2833 HIV-negative women and 241 WLWH attending multicentric studies in Latin America (ESTAMPA study), and in Africa (CESTA study). Oncoprotein positivity were evaluated at each testing site, according to HIV status as well as type-specific agreement with HPV-DNA results. A feedback questionnaire was given to the operators performing the oncoprotein test to evaluate their impression and acceptability regarding the test. The OncoE6/E7 test revealed a high positivity rate heterogeneity across all testing sites (I2: 95.8%, p < .01) with significant lower positivity in WLWH compared to HIV-negative women (12% vs 25%, p < .01). A similar HPV-type distribution was found between HPV DNA genotyping and oncoprotein testing except for HPV31 and 33 (moderate agreement, k = 0.57). Twenty-one laboratory technicians were trained on oncoprotein testing. Despite operators' concerns about the time-consuming procedure and perceived need for moderate laboratory experience, they reported the OncoE6/E7 test as easy to perform and user-friendly for deployment in resource-limited settings. The high positivity rate variability found across studies and subjectivity in test outcome interpretation could potentially results in oncoprotein false positive/negative, and thus the need for further refinements before implementation of the oncoprotein testing in screen-triage-and-treat approaches is warranted.